Gender differences in clinical and biochemical parameters among patients hospitalized for schizophrenia: towards precision medicine - Esposito, Cecilia Maria; De Cagna, Francesca; Caldiroli, Alice; Capuzzi, Enrico; Ceresa, Alessandro; Di Paolo, Martina; Auxilia, Anna Maria; Capellazzi, Martina; Tagliabue, Ilaria; Cirella, Luisa; Clerici, Massimo; Brondino, Natascia; et al. (European archives of psychiatry and clinical neuroscience, 2024)
Background The scientific literature shows some gender differences in the clinical course of schizophrenia. The aim of this study is to identify gender differences in clinical and biochemical parameters in subjects affected by schizophrenia. This would allow for the implementation of individualized treatment strategies. Methods We examined a large set of clinical and biochemical parameters. Data were obtained from clinical charts and blood analyses from a sample of 555 schizophrenia patients consecutively admitted for exacerbation of symptoms to the inpatient clinic of Fondazione IRCCS Policlinico (Milan) or ASST Monza in Italy from 2008 to 2021. Univariate analyses, binary logistic regression, and a final logistic regression model were performed with gender as dependent variable. Results The final logistic regression models showed that male patients (compared to females) were more prone to lifetime substance use disorders (p = 0.010). However, they also had higher GAF (global functioning) mean scores (p < 0.001) at the time of hospitalization. Univariate analyses showed that male patients (with respect to females) had an earlier age at onset (p < 0.001), a more frequent family history of multiple psychiatric disorders (p = 0.045), were more often smokers (p < 0.001), had a more frequent comorbidity with at least one psychiatric disorder (p = 0.001), and less often suffered from hypothyroidism (p = 0.011). In addition, men had higher levels of albumin (p < 0.001) and bilirubin (t = 2.139, p = 0.033), but lower levels of total cholesterol (t = 3.755, p < 0.001). Conclusions Our analyses indicate a less severe clinical profile in female patients. This is evident especially in the early years of the disorder, as suggested by less comorbidity with psychiatric disorders or later age at onset; this is consistent with the related literature. In contrast, female patients seem to be more vulnerable to metabolic alterations as demonstrated by more frequent hypercholesterolemia and thyroid dysfunction. Further studies are needed to confirm these results in the framework of precision medicine.